Kontribusi Kepemimpinan Laissez-Faire, Sarana dan Prasarana, Kepuasan Kerja, dan Ketahanmalangan Terhadap Komitmen Organisasional Guru Sekolah Dasar di Kabupaten Mimika, Papua - I.N.P.B. Trisna; A.A.G. Agung; I.P.W. Ariawan (Jurnal Administrasi Pendidikan Indonesia, 2022)
This research aims to determine the contribution of Laissez-Faire leadership, school facilities, job satisfaction, and adversity quotient towards teachers’ organizational commitment. The sample of this study was 76 primary school teachers in the regency of Mimika, Papua province. This study is classified as ex-post-facto with descriptive statistics analysis, simple correlation, partial correlation, multiple correlation, and multiple regression data analysis design. Data collection for this study was conducted by using the Five-point Likert scale questionnaire model. The results of the study show that: 1) There is a negative and significant correlation between Laissez-Faire leadership and organizational commitment with 0,294 (ryx1) product moment coefficient correlation, 0,192 (ry.x1-x2,3,4) partial correlation coefficient, and 6,14% contribution of Laissez-Faire leadership towards organizational commitment, 2) There is a positive and significant correlation between school facilities and organizational commitment with 0,605 (ryx2) product moment coefficient correlation, 0,412 (ry.x2-x,3,4) partial correlation coefficient, and 27,00% contribution of school facilities towards organizational commitment, 3) There is a negative and significant correlation between job satisfaction and organizational commitment with 0,558 (ryx3) product moment coefficient correlation, 0,325 (ry.x3-x1,2,4) partial correlation coefficient, and 11,00%, contribution of job satisfaction towards organizational commitment, 4) There is a negative and insignificant correlation between adversity quotient and organizational commitment with 0,241 (ryx4) product moment coefficient correlation, 0,190 (ry.x4-x1,2,3) partial correlation coefficient, and 1,73%, contribution of adversity quotient towards organizational commitment, 5) There is a positive and significant correlation of Laissez-Faire leadership, school facilities, job satisfaction, adversity quotient, and organizational commitment with Ry.1234 multiple correlation coefficient of 0,677 and there is a contribution of Laissez-Faire leadership, school facilities, job satisfaction, adversity quotient, and organizational commitment simultaneously by 45,9%.